Leadership Identity Development Through Reflection and Feedback in Team-Based Learning Medical Student Teams. Issue 1 (2nd January 2018) - Alizadeh, Maryam; Mirzazadeh, Azim; Parmelee, Dean X.; Peyton, Elizabeth; Mehrdad, Neda; Janani, Leila; Shahsavari, Hooman
ABSTRACT: Problem : Studies on leadership identity development through reflection with Team-Based Learning (TBL) in medical student education are rare. We assumed that reflection and feedback on the team leadership process would advance the progression through leadership identity development stages in medical students within the context of classes using TBL. Intervention : This study is a quasi-experimental design with pretest–posttest control group. The pretest and posttest were reflection papers of medical students about their experience of leadership during their TBL sessions. In the intervention group, TBL and a team-based, guided reflection and feedback on the team leadership process were performed at the end of all TBL sessions. In the other group, only TBL was used. The Stata 12 software was used. Leadership Identity was treated both as a categorical and quantitative variable to control for differences in baseline and gender variables. Chi-square, t tests, and linear regression analysis were performed. Context : The population was a cohort of 2015–2016 medical students in a TBL setting at Tehran University of Medical Sciences, School of Medicine. Teams of four to seven students were formed by random sorting at the beginning of the academic year (intervention group n = 20 teams, control group n = 19 teams). Outcome : At baseline, most students in both groups were categorized in the Awareness and Exploration stage of leadership identity: 51 (52%) in the intervention group and 59 (55%) in the control group: uncorrected χ 2 (3) = 15.6, design-based F (2.83, 108) = 4.87, p = .003. In the posttest intervention group, 36 (36%) were in exploration, 33 (33%) were in L-identified, 20 (20%) were in Leadership Differentiated, and 10 (10%) were in the Generativity. None were in the Awareness or Integration stages. In the control group, 3 (20%) were in Awareness, 56 (53%) were in Exploration, 35 (33%) were in Leader Identified, 13 (12%) were in Leadership Differentiated. None were in the Generativity and Integration stages. Our hypothesis was supported by the data: uncorrected χ 2 (4) = 18.6, design-based  F (3.77, 143) = 4.46, p = .002. The mean of the leadership identity in the pretest, intervention group equaled 1.93 ( SD = 0.85) and the pretest, control group mean was 2.36 ( SD = 0.86), p = .004. The mean of the posttest, intervention group was 3.04 ( SD = 0.98) and posttest, control group mean was 2.54 ( SD = 0.74), T = −4.00, design df = 38, p < .001, and adjusted on baseline and gender T = −8.97, design df = 38, p < .001. Lessons Learned : Reflection and feedback on the team leadership process in TBL advances the progression in stages of leadership identity development in medical students. Although the TBL strategy itself could have an impact on leadership identity development, this study demonstrates that when a reflection and feedback on leadership intervention are added, there is much greater impact.